The novel ADAMTS13‐p.D187H mutation impairs ADAMTS13 activity and secretion and contributes to thrombotic thrombocytopenic purpura in mice. (17th January 2015) - De Cock, E.; Hermans, C.; De Raeymaecker, J.; De Ceunynck, K.; De Maeyer, B.; Vandeputte, N.; Vandenbulcke, A.; Deckmyn, H.; Rottensteiner, H.; De Maeyer, M.; De Meyer, S. F.; Vanhoorelbeke, K.
Summary Background Congenital thrombotic thrombocytopenic purpura (TTP) is characterized by mutations in the ADAMTS13 gene, which either impair protein secretion or influence ADAMTS13 (A Disintegrin‐like And Metalloprotease domain with ThromboSpondin type‐1 motif, member 13) activity. Phenotypic consequences of these mutations have not yet been evaluated in animal models for TTP. Objectives To identify the in vitro effect of a novel ADAMTS13 mutation and to investigate whether this mutation induces TTP in vivo. Methods All 29 ADAMTS13 exons with exon–intron boundaries of a patient with pregnancy‐onset TTP were sequenced. Wild‐type and mutant ADAMTS13 proteins were both transiently and stably expressed in human embryonic kidney cells, and their activity was evaluated in vitro using fluorescence resonance energy transfer and flow assays. Molecular dynamics simulations were performed to study Ca2+ stability. Adamts13–/– mice were hydrodynamically injected with wild‐type and mutant expression plasmids and triggered with recombinant human von Willebrand factor. Results We identified a novel heterozygous c.559G>C mutation in exon 6 of the proposita's ADAMTS13 gene. This mutation resulted in a p.Asp187His substitution (p.D187H), which was located in the high affinity Ca2+‐binding site in the metalloprotease domain of ADAMTS13. The homozygous p.D187H mutation down‐regulated ADAMTS13 activity in vitro. Impaired proteolytic activity was linked to unstable Ca2+ binding as visualized using a molecular dynamics simulation. In addition, the p.D187H mutation affects protein secretion in vitro. In Adamts13–/– mice, the homozygous p.D187H mutation reduced ADAMTS13 secretion and activity and contributed to TTP when these mice were triggered with recombinant human von Willebrand factor. Conclusions Our data indicate that the p.D187H mutation impairs ADAMTS13 activity and secretion and is responsible for TTP onset in mice.